2018
DOI: 10.3389/fneur.2018.00951
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Degeneration of the Vagus Nerve in Parkinson's Disease—A High-Resolution Ultrasound Study

Abstract: Background: Recent histopathological studies revealed degeneration of the dorsal motor nucleus early in the course of Parkinson's disease (PD). Degeneration of the vagus nerve (VN) axons following neurodegeneration of brainstem vagal nuclei should be detectable by high-resolution ultrasound (HRUS) as a thinning of the VNs.Methods: We measured both VNs cross-sectional area (VN-CSA) of 35 patients with PD and 35 age- and sex-matched healthy controls at the level of the thyroid gland using HRUS.Results: On both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
61
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 13 publications
12
61
2
1
Order By: Relevance
“…Vagus nerve sonography has been performed in HCs in different countries. The CSA values in HC vary among studies, with the mean ranging from 1.6 to 5.88 mm 2 1–5,7–10 . These differences may be partly attributed to different ethnicities and different methods of assessing CSA 14 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Vagus nerve sonography has been performed in HCs in different countries. The CSA values in HC vary among studies, with the mean ranging from 1.6 to 5.88 mm 2 1–5,7–10 . These differences may be partly attributed to different ethnicities and different methods of assessing CSA 14 .…”
Section: Discussionmentioning
confidence: 98%
“…The vagus nerve, which contains parasympathetic fibers, is different from spinal nerves. Vagus nerve sonography has been performed in healthy controls (HCs), 1,2 Charcot‐Marie‐Tooth Type 1B (CMT1B), 3 chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), 4 multifocal motor neuropathy, 5,6 amyotrophy lateral sclerosis, 5 diabetes mellitus, 7 and Parkinson disease 8–10 . The cross‐sectional area (CSA) values in HC vary among different studies, with the mean ranging 1.60‐5.88 mm 2 1–5,7–10 .…”
Section: Introductionmentioning
confidence: 99%
“…Mapping the significant SNPs to the gene domain of the hg38 reference genome in a 10 kb interval [22], the GO enrichment results showed that six biological functional regions were significantly enriched (Bonferroni-corrected p-value < 8 × 10 −3 , Supplementary Table S1). Four significantly enriched biologically functional regions have been reported to be associated with PD, including the axon [23], neuron-to-neuron synapse [24], asymmetric synapse [25] and gamma aminobutyric acid (GABA)-ergic synapse [26] (Figure 2). Therefore, these results indicate that the meta-analysis of GWAS data reflects the pathological features of PD.…”
Section: Screening Snps Of Pd Based On Meta-analysis Gwas Datamentioning
confidence: 99%
“…Interestingly, objective imaging techniques were found to be more sensitive than subjective ratings of patients (Knudsen et al, 2017a). Additionally, sonographic studies confirm a direct impairment of the vagal nerve by displaying nerve atrophy with high-resolution ultrasound (Pelz et al, 2018;Walter et al, 2018).…”
Section: Gastrointestinal Symptoms In Pd: Indications For a Start Of mentioning
confidence: 93%